Analysis of BTS Capacity in Meeting the Information Needs of Border Communities: A Case Study of Internet Network Instability in Kawaluso, Sangihe Islands - Israel, Ella Helmy; Papuas, Alfrianus; Maluenseng, Jackried Kanselir; Sehang, Steve Arthur (Bahasa Indonesia, 2025)
The instability of internet access in Kawaluso, Sangihe Islands, an Indonesian-Philippine border island, is thought to hinder fulfilling the community's information needs. This research analyzes the root of the problem through three approaches: (1) Fresnel Zone for physical bottleneck evaluation, (2) bandwidth allocation, and (3) Committed Information Rate (CIR). Results showed no significant physical interference (Fresnel Zone: 79.01 m) and adequate individual bandwidth allocation (33.33 Mbps downlink/day). However, when 135 users accessed simultaneously, the CIR dropped dramatically to 0.74 Mbps/user, far below the Indonesian broadband standard (2 Mbps). Key findings revealed user overcapacity (demand-capacity ratio: 135%) as the leading cause of instability, not geographical or infrastructure factors. The study recommends: (a) an increase in BTS capacity to 270 Mbps, (b) implementation of Quality of Service (QoS) for critical service priorities, and (c) load balancing between operators. Policy implications emphasize adjusting BTS capacity to projected users in remote areas.